2019
DOI: 10.1016/j.heliyon.2019.e02807
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cellulose nanocrystals from bamboo shoots using Response Surface Methodology

Abstract: Cellulose-based advanced materials, such as cellulose nanocrystals (CNC), have high potential application for drug delivery system. In this study, the CNC were produced from bamboo shoots using acid hydrolysis process. The delignification of bamboo shoots was conducted using alkali and hydrogen peroxide pretreatment processes. The operating condition of the production of CNC from bamboo shoots was optimized using Response Surface Methodology (RSM) based on the yield and crystals recovery as the responses. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 44 publications
3
26
1
1
Order By: Relevance
“…CNCs were prepared using the previously established method. 39 A total of 10 g of BS powder was added into 200 mL of sodium hydroxide solution 20% (w/v) while the solution was heated at 90 °C and kept for 4 h under stirring. Then, it was continued by the bleaching process using 25 mL of sodium hydroxide solution 4% (w/v) at 50 °C while the same amounts of hydrogen peroxide 50% were added dropwise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CNCs were prepared using the previously established method. 39 A total of 10 g of BS powder was added into 200 mL of sodium hydroxide solution 20% (w/v) while the solution was heated at 90 °C and kept for 4 h under stirring. Then, it was continued by the bleaching process using 25 mL of sodium hydroxide solution 4% (w/v) at 50 °C while the same amounts of hydrogen peroxide 50% were added dropwise.…”
Section: Methodsmentioning
confidence: 99%
“…The optimum condition from the previous study was applied in this study to obtain a consistent product. 39 PBSs were hydrolyzed using sulfuric acid solution 55 wt % with a PBS mass to sulfuric acid solution ratio of 1:20 at 40 °C for 60 min. To stop the hydrolysis process, 10-fold cold-distilled water was poured into the solution.…”
Section: Methodsmentioning
confidence: 99%
“…These vary upon their sizes and functionality (Abitbol et al, 2016). Amiralian et al, 2015;Kang et al, 2017;Wijaya et al, 2019 Cellulose Nano-Fibrils (CNFs)…”
Section: Nano-cellulose Types and Propertiesmentioning
confidence: 99%
“…These fibers convert/disintegrate into a crystalline, rod-shaped, and nano-sized units, such as much as micrometers, called Cellulose Nano-Crystal (CNC). However, the nano-sized compound can be produced using a microbial approach called bacterial nanocellulose (BNC) (Wijaya et al, 2019). Numerous studies have reported on Cellulose Nano-Fibril and CNC extraction from different types of sources such as bamboo, cotton, sugar beet, banana rachis, and agricultural waste, including hardwood and softwood (Haldar and Purkait, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have examined bamboo shoots. Cellulose nanocrystals and cellulose nanofibrils can be prepared from bamboo shoots by acid hydrolysis, which can be used in the fields of composite materials, drug delivery, and emulsifiers ( Wijaya et al, 2019 ; Huang et al, 2020 ; Wang et al, 2020 ). Water-insoluble bamboo shoot dietary fiber was used as a plant food particle stabilizer to produce stable oil-in-water (O/W) Pickering emulsions ( He et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%